Inequalities for the Fractional Derivatives of Trigonometric Polynomials in Spaces with Integral Metrics - Kolomoitsev, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We establish necessary and sufficient conditions for the validity of Bernstein-type inequalities for the fractional derivatives of trigonometric polynomials of several variables in spaces with integral metrics. The problem of sharpness of these inequalities is investigated.